Fixed Points, Common Fixed Points and Invariant Approximation: Sumit Chandok, T.D. Narang - Team, Support (Thai Journal of Mathematics, 2014)
Some new fixed point and common fixed point theorems for nonexpansive and generalized nonexpansive mapppings have been proved in the framework of metric spaces. Invaraint approximation results have been obtained for these types of mappings as applications. Our results generalize and extend several known results available in the literature.